Go Digital: Edukasi dan Sosialisasi Fintech untuk UMKM Pasar Tradisional Kanoman - Aan Kanivia; Dessy Kumala Dewi; Kevin Vallenski; Debby Zaqiara Yazwa; Nayla Sausan Fa’alihah (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
The rapid development of digital technology has significantly transformed economic activities, particularly payment systems used by Micro, Small, and Medium Enterprises (MSMEs). The implementation of financial technology (fintech), especially the Quick Response Code Indonesian Standard (QRIS), offers advantages including transaction efficiency, improved financial recording, and increased financial inclusion. However, digital payment adoption among MSMEs in traditional markets remains relatively low due to limited digital literacy, strong dependence on cash transactions, and concerns regarding transaction security. These conditions are evident among MSMEs in Pasar Kanoman, Cirebon City, where most traders still rely on conventional payment methods despite access to basic digital devices. This community service program aims to enhance understanding, awareness, and readiness of MSMEs to adopt fintech through QRIS utilization as a digital payment system. The program was implemented through structured educational sessions, socialization activities, interviews, and direct mentoring tailored to the needs and characteristics of traditional market traders. A participatory approach encouraged active involvement and ensured knowledge could be practically applied in daily business activities. The results show improved understanding of QRIS functions, benefits, and operational mechanisms, along with more positive attitudes and increased interest in digital payment adoption. Overall, the program strengthens financial literacy and supports sustainable inclusion.